Entre peles: memorial de um processo de criação em arte - Barbosa, Kenner Lucas Prado (2015)
The research "Between Skins: memorial of a process of creating art" is anchored in the search line Practice and Processes in Art, specifically in the field of Poetic Image. It is a set of experimental actions in interconnection between artistic languages. The design, tattoo, photography, printmaking, performance and the creation of the artistic object permeate the artistic research, featuring the hybrid profile of the same. The argumentative text presents the practical relations with the theoretical references with contemporary art and describes the process of creation from the first intentions in seeking to subvert and reinvent the practice of tattooing to the relationships that arise between art and everyday life. Also presented reproductions of images that are the result of research and documents the exhibition of works of conclusive research.